Thickness measurement of worn molar cusps by ultrasound - TAĞTEKİN, DİLEK; YANIKOĞLU, FUNDA (KARGER, 2005)
This study aimed to evaluate the effectiveness of an ultrasonic system for in vitro measurement of cusp tips of human teeth. Each worn cusp of 12 molar teeth was measured with an industrial ultrasonic system. The teeth were sectioned and measured by polarized light microscopy. The ultrasonic measurements and histological readings were moderately correlated (r = 0.601, p < 0.01). The ultrasonic system used in this study seemed a promising method for measuring thickness of worn cusp tips of extracted human molar teeth. Copyright (C) 2005 S. Karger AG, Basel.
Keywords: enamel; thickness; tooth wear; ultrasound; HUMAN-ENAMEL; WEAR; ATTRITION; EROSION; DENTIN